2010
DOI: 10.1371/journal.pone.0013641
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Influence on the Cortical Processing of Experimental Pain and the Moderating Effect of Pain Status

Abstract: BackgroundResearch suggests that the COMT Val158Met, BDNF Val66Met and OPRM1 A118G polymorphisms moderate the experience of pain. In order to obtain experimental confirmation and extension of findings, cortical processing of experimentally-induced pain was used.MethodA sample of 78 individuals with chronic low back pain complaints and 37 healthy controls underwent EEG registration. Event-Related Potentials were measured in response to electrical nociceptive stimuli and moderation by COMT Val158Met, BDNF Val66M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 43 publications
1
43
1
2
Order By: Relevance
“…Thus, the adrenergic-related ADRB2 and COMT have been associated with autonomic dysregulation [34], sleep dysfunction [35], and anxiety [36], as well as with pain processing [37]. Similarly, serotoninergic-related genes such as SLC6A4 and HTR2A have been associated with depression and anxiety in FMS patients [38].…”
Section: Role Of the Catechol-o-methyltransferase Gene Polymorphism Imentioning
confidence: 99%
“…Thus, the adrenergic-related ADRB2 and COMT have been associated with autonomic dysregulation [34], sleep dysfunction [35], and anxiety [36], as well as with pain processing [37]. Similarly, serotoninergic-related genes such as SLC6A4 and HTR2A have been associated with depression and anxiety in FMS patients [38].…”
Section: Role Of the Catechol-o-methyltransferase Gene Polymorphism Imentioning
confidence: 99%
“…For a detailed description of the protocol, we refer to Vossen et al, 2010aVossen et al, & 2011 Here, a summary of the design is given. Seventy-six pain-free subjects and 75 patients with chronic low back pain participated in the study.…”
Section: Methodsmentioning
confidence: 99%
“…In a more recent study, we investigated the influence of the COMT Val158Met, BDNF Val66Met, and BDNF Val66Met polymorphisms on pain using ERPs (Vossen et al, 2010a). The sample of this study consisted of chronic low back pain patients, as well as healthy controls.…”
Section: The Influence Of Gene Polymorphisms On Pain-evoked Potentialsmentioning
confidence: 99%
“…Vossen et al [27] recently reported that despite there being no relationship between rs4680 and cortical processing in response to experimental pain stimuli, there was a significant interaction with pain status. Individuals with chronic LBP carrying the M allele had a significantly different response to experimental pain than those with the M allele who were pain free, but again the number of individuals included in the study was small (n =78 LBP and n = 37 healthy individuals) [27].…”
Section: Catechol-o-methyltransferase (Comt)mentioning
confidence: 99%